2015
DOI: 10.1039/c4cp03162h
|View full text |Cite
|
Sign up to set email alerts
|

The dielectric study of insulin-loaded reverse hexagonal (HII) liquid crystals

Abstract: The dielectric behavior of the insulin-loaded HII mesophase (containing GMO-TAG-water-glycerol-insulin) was studied using two empty reference systems (GMO-TAG-water and GMO-TAG-water-glycerol) at a frequency range of 10(-2)-10(6) Hz, and a temperature range of 290-333 K. Three clearly defined relaxation processes were observed and assigned to the reorientation of GMO polar heads, the tangential movement of counterions at the interface, and the movements of TAGs through the lipid tail. Upon addition of glycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…54 However, H II phase consists of densely packed inverted micelles in hexagonal cylindrical fashion (Scheme 1). 18 Thus, from the geometrical architectures, it is clear that H II phase provides most restricted pathway for the proton during "Grotthuss" mechanism of proton diffusion. However, the diamond Pn3m phase can provide the faster pathway for proton diffusion due to tetrafold water channel connectivity, rather than trifold connectivity in Ia3d phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 However, H II phase consists of densely packed inverted micelles in hexagonal cylindrical fashion (Scheme 1). 18 Thus, from the geometrical architectures, it is clear that H II phase provides most restricted pathway for the proton during "Grotthuss" mechanism of proton diffusion. However, the diamond Pn3m phase can provide the faster pathway for proton diffusion due to tetrafold water channel connectivity, rather than trifold connectivity in Ia3d phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Each cylinder of H II phase is a topologically inverted “water-in-oil” version, where the aqueous domain is densely packed infinitely long, water filled straight rods (Scheme ). However, Ia3d (gyroid type) and Pn3m (diamond type) phases exhibit inverse (type II) and bicontinuous structure. These inverse bicontinuous structures of both cubic phases adopt “minimal surface” (mean curvature is zero), which is extended to fill space periodically in different modes (gyroid mode in Ia3d and diamond mode in Pn3m) .…”
Section: Introductionmentioning
confidence: 99%
“…The fluid lamellar phase consists of amphiphilic bilayers separated by water domains and closely resembles the cellular membranes . The H II phase is a topologically inverted “water in oil” system comprising infinitely long and straight water filled rods packed densely in a nonpolar matrix of lipophilic chains. , The inverse bicontinuous cubic phases, namely, gyroid ( Ia 3 d ) and diamond ( Pn 3 m ), are formed by the arrangement of a continuous lipid bilayer on mathematical minimal surfaces (Scheme ). , In Ia 3 d mesophase, two water networks join in a 3 × 3 junction at an angle of 120°, and in Pn 3 m , they join in a 4 × 4 manner at a tetrahedral angle of 109.5° .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its unique structural properties, H II mesophase has been used as an excellent carrier for important drug molecules such as Desmopressin, sodium diclofenac, , and cyclosporine A . Moreover, due to excellent biocompatibility of H II mesophase, it provides the new opportunities to deliver biomolecules such as insulin, , lysozyme, peptides, proteins, and DNA , to their active sites. Furthermore, it was found that the inner diameter of the water cylinder is sufficient to load the hydrophilic dendrimer, which might have potential application for dendrimer coupled drug delivery vehicles …”
Section: Introductionmentioning
confidence: 99%